Enhanced Performance of Induction Motors Using a 3-Level H-Bridge Space Vector PWM Inverter - Shukla, Darshni; Panchal, Brijal; Nema, Pragya (Current Approaches in Engineering Research and Technology Vol. 10, 2024)
Multilevel voltage-fed inverters utilizing Space Vector Pulse Width Modulation (SVPWM) have gained significant traction in high-power, high-performance industrial drive applications due to their improved DC bus utilization and enhanced output waveform quality. In this Chapter, a 3-level SVPWM H-bridge inverter is proposed, offering a greater number of switching states compared to traditional 2-level Voltage Source Inverters (VSI). The step-by-step methodology outlined here provides a detailed approach that can be adapted for higher-level multilevel inverters as well. MATLAB/SIMULINK implementation, along with experimental results, is presented to validate the inverter’s operation within the linear modulation region. The Fast Fourier Transform (FFT) analysis is also included, showcasing the harmonic performance of the inverter. Additionally, the proposed inverter configuration demonstrates improved efficiency and reduced total harmonic distortion (THD), making it suitable for a wide range of industrial applications. This study highlights the potential for future scalability to higher-level inverters, ensuring flexibility in design for evolving power system requirements.